Analysis of the Impact of Social Media Use on Students' Interpersonal Communication Patterns - Fitri Aisyah Ritonga; Anda Yanny (Edumaniora : Jurnal Pendidikan dan Humaniora, 2026)
The development of social media has brought significant changes in the way individuals communicate, particularly among university students. This study aims to analyze the influence of social media use on interpersonal communication patterns of students in the Communication Studies Program at the State Islamic University of North Sumatra. Using a qualitative approach with descriptive methods, data were collected through in-depth interviews with purposively selected informants. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that the use of social media as a means of communication has a significant influence on aspects of openness, empathy, support, positive attitudes, and equality in students' interpersonal communication.